Zinc Oxide Nanostructures for Efficient Energy Conversion in Organic Solar Cell - Nurfazliana, M.F.; Kamaruddin, S.A.; Alias, M.S.; Nafarizal, N.; Saim, H.; Sahdan, M.Z. (Journal of Technology Innovations in Renewable Energy, 2014)
We present a new approach of solution-processed using zinc oxide (ZnO) nanostructures as extraction layer material for organic solar cells. It is low chemical reaction compatibility with all types of organic blends and its good adhesion to both surfaces of ITO/glass substrate and the active layer (blends). Parameters such as the thickness and the morphology of the films were investigated to prove that these factors greatly affect the efficiency of organic solar cells. In this work, ZnO layer with thickness of approximately 53 nm was used as an interlayer to prevent pin-holes between the electrode and the polymer layer. The polymer layer was coated on the ZnO layer with the thickness of about 150 nm. The thick polymer layer will form a non-uniform surface because of the solvent, 1-2dichlorobenzene will etch away some region of the polymer layer and forming pin-holes. ZnO nanostructures layer was used to prevent pin-holes between the polymer layer and electrode. From the surface morphology of ZnO layer, it shows a uniform surface with particle grain size obtained between 50 -100 nm. The presence of the interlayer has a positive effect on the electrical characteristics of the solar cells. It was found that an organic solar cell with thickness less than 150 nm shows the optimum performance with efficiency of 0.0067% and Fill Factor (FF) of about 19.73.